Confirming the presence of Zimiris doriae Simon, 1882 (Araneae: Prodidomidae) in Venezuela and list of the spider species introduced in the country - Osvaldo Villarreal; David Chamé-Vázquez (Revista Chilena de Entomología)
The spider Zimiris doriae Simon, 1882, is recorded for the first time in Venezuela, based on a female specimen collected inside a house at La Victoria, Aragua state. Furthermore, a preliminary list of 10 families and 24 introduced spider species found in Venezuela is provided.